Fractional microneedle radiofrequency - mechanism of action and assessment of safety, effectiveness in the treatment, and possible side effects based on a review of scientific literature - Nowak, Aleksandra; Nowak, Alicja; Bogusz, Klaudia; Cywka, Łucja; Baran, Natalia; Bielak, Adriana; Szwed, Weronika; Maksymowicz, Marcela; Machowiec, Piotr (Journal of Education, Health and Sport, 2023)
Introduction and purpose: For all skin types, micro-needle radiofrequency (FMR) can be a safe and effective aesthetic medicine procedure for the treatment of various dermatological and aesthetic conditions. The aim of the study is to present the mechanism of action and assess safety, treatment efficacy, and possible side effects on the basis of a review of the scientific literature. Description of the state of knowledge: FMR uses micro-needles to penetrate the skin to a depth of up to 4.5 mm and deliver radiofrequency current in a fractional manner, producing the controlled fractions of micro-injuries in the dermis, inducing neocollagenesis, neoelastinogenesis, and angiogenesis. FMR has a wide range of positive effects such as skin rejuvenation, skin tightening, facial and body scar remodeling, and hair growth through transdermal collagen induction. Summary: Increasingly, patients are looking for minimally invasive methods of skin tightening and fat remodeling. In response, Aesthetic Medicine has proposed a combination of two techniques, micro-needling and radiofrequency. As more and more studies are showing the effectiveness and efficiency of this procedure, also emphasizing its safety, minimal risk of serious side effects, and ease of use, micro-needle radiofrequency is being proposed as an attractive answer to people’s desires for a less invasive method of skin rejuvenation. However, further research in this area is needed to optimize the parameters of the treatment to achieve the best results.